2013
DOI: 10.1093/cvr/cvs423
|View full text |Cite
|
Sign up to set email alerts
|

Nandrolone attenuates aortic adaptation to exercise in rats

Abstract: These results demonstrate that nandrolone attenuates aortic adaptations to exercise by regulating mitochondrial dynamic remodelling, including down-regulation of mitochondrial biogenesis and intensive autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Fusion/fission balance plays an important role in determining the fate of depolarized mitochondria (16, 17) and if altered, can produce dysfunctional or damaged mitochondria that are subsequently degraded by autophagy. Our data shows that NLRP3 −/− lungs had exaggerated induction of mitochondrial fusion proteins MFN1, MFN2 and OPA1 during hyperoxia compared to WT lungs, which was blunted in the absence of PINK1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fusion/fission balance plays an important role in determining the fate of depolarized mitochondria (16, 17) and if altered, can produce dysfunctional or damaged mitochondria that are subsequently degraded by autophagy. Our data shows that NLRP3 −/− lungs had exaggerated induction of mitochondrial fusion proteins MFN1, MFN2 and OPA1 during hyperoxia compared to WT lungs, which was blunted in the absence of PINK1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Chaves et al [15,16] showed that in spite of the beneficial effect of HIE on the heart through increased activity of antioxidant enzymes, Nandrolone administration induced lower SOD, GPx and glutathione reductase (GR) activity when compared to control and trained animals. Similarly, Sun et al [59] demonstrated that the combination of Nandrolone and an aerobic physical training increased MDA and PCC, and decreased SOD and NQO-1 protein levels on aortic large vessels. On the other hand, Saborido et al [54] observed that Stanozolol administration might protect rat gastrocnemius mitochondria against oxidative damage of proteins and changes in membrane fatty acid composition induced by acute exercise.…”
Section: High-intensity Exercise Anabolic Androgenic Steroids and Brmentioning
confidence: 87%
“…Adenoviral‐medi‐ated expression of HO‐1 inhibited DISC formation and caspase 3/9 activation, diminished the expression of Beclin‐1, and partially inhibited the processing of LC3B‐I to LC3B‐II in cigarette smoke‐exposed epithelial cells, Aerobic training increased HO‐1 levels, induced mitochondrial complexes I and V, increased mitochondrial DNA copy number, and also increased conversion of LC3‐I to LC3‐II ( i.e. , increased autophagy), which resulted in improved ace‐tylcholine‐induced vascular relaxation (47). HO‐1 promotes autophagy and elimination of damaged mitochondria in order to repress oxidative stress in LPS‐treated rat liver (48).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial fission and fusion involve 4 dynamin‐related GTPase family proteins, including MFN1, MFN2, OPA1, and DRP1. Fusion/fission balance plays an important role in determining the fate of depolarized mitochondria (24, 57). Fusion/fission imbalance can lead to dysfunctional or damaged mitochondria and subsequent degradation by autophagy.…”
Section: Discussionmentioning
confidence: 99%